Agroecosystems Very Complex Environmental Systems - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2021)
This book, "Agroecosystems - Very Complex Environmental Systems", aims to present an update on different aspects associated with the importance of sustainable agriculture. It was our intention to gather information from diverse sources in this volume and to give some real-life examples, extending the appreciation of the complexity of this subject in a way that may stimulate new approaches in relevant fields.